Factors Influencing Financial Institutions’ Participation in Tourism Project: Case of Lagos Street Carnival. - Obadeyi, J. A; I. O., Adesuyi; Okhiria, Adebimpe. O; Abutu, Grace. N (Advances in Social Sciences Research Journal, 2019)
The purpose of the paper is to examine factors that influence financial institutions’ participation in tourism project; case of Lagos street carnival. The clamour for diversification by Nigerian government since the decline of crude oil price towards the last quarter of 2015 has provided a platform indirectly to look at other direction that is full of natural endowment opportunities, but the opportunity remains untapped since the discovery of crude oil in the 70s’. Hence, the untapped opportunity is the tourism sub-sector. Tourism is a socio-economic tool for poverty alleviation, means of creating awareness about ways of life of people within a settlement and increase income generation. For financial institutions to participate successfully in tourism project, it requires financial support from financial institutions to showcase, promote, uplift and to financially-support the nourished culture, norms and values the people cherish; and to ensure that the beliefs of the people are not eroded by foreign culture and above all, to stimulate the economy. The primary source of data is adopted via structured questionnaire. Statistically, the estimated parameter are mean, standard deviation, and standard error (ẟ√N). The responses of the respondents gathered via the questionnaire will be analysed using the Statistical Package for Social Sciences (SPSS). The result shows that most of social -people participate in different tourism –related festivals (e.g. eyo, igunuko etc.), which has led to the sustainability and development of the society, and courtesy of financial institutions’ participation has helped to provide funds to further create awareness about the traditions, beliefs and values of Lagos indigenes, who are otherwise known as Lagosians. The study recommends that policymakers should invest immensely in tourism industry in order to enrich the socio-economic and geographical life patterns of the people in the coast area via the support of financial institutions by way of channelling funds to the tourism sub-sector in order to prevent cultural extinction. Also, government should establish institutions (ministries, departments and agencies) to strengthen and defend acquired tourism trade rights in Nigeria.